Follow Up on Simple (Closed) Extraction of Fractured Maxillary Canine Teeth in Domestic Ferrets (Mustela putorius furo) - Primožič, Pia Kristina; Žagar, Žiga; Šmalc, Klemen; Račnik, Joško; Švara, Tanja; Nemec, Ana (Frontiers in Veterinary Science, 2021)
Fractured canine teeth (especially maxillary canine teeth) are common in domestic ferrets (Mustela putorius furo). We evaluated (detailed oral/dental and radiographic examination under general anesthesia) 18 domestic ferrets affected by 23 complicated crown fractures of periodontally healthy permanent maxillary canine teeth over a 2-year period. Average age of the ferrets at the time of diagnosis was 2.6 years. Only three teeth were discolored on clinical examination. Out of 23 teeth, 22 were radiographically evaluated. No radiographic evidence of endodontic disease was observed in 11/22 canine teeth. Inflammatory root resorption was observed in 5/22, periapical lucency in 5/22 teeth, apical widening of periodontal ligament space in 6/22 teeth, and failure of the pulp cavity to narrow in 3/22 teeth. All animals were treated by simple (closed) extraction of the affected teeth. Histological examination of eight teeth was performed. Pulp appeared histologically vital in five (3/5 showed no radiographic evidence of endodontic disease), pulpitis was diagnosed in two (both without radiographic evidence of endodontic disease) and pulp necrosis in one case (dental radiographs revealed apical widening of periodontal ligament space and failure of the pulp cavity to narrow). All extraction sites healed uneventfully by the 2-week recheck examination. Long-term follow-up revealed development of post-extraction upper lip entrapment with mandibular canine tooth in eight out of 18 ferrets, which appeared clinically irrelevant. According to clients seven out of 18 ferrets showed an improved quality of life. Simple tooth extractions are warranted in ferrets affected by complicated crown fracture of the periodontally healthy permanent maxillary canine teeth.